Analisis Dasar Hukum dan Implementasi Arbitrase Syariah Sebagai Alternatif Penyelesaian Sengketa dalam Perspektif Undang-Undang Nomor 30 Tahun 1999 - Kaia Hati; Muhammad Rafi Athaya Santoso; Tegar Bayu Adjie Surono (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Sharia arbitration constitutes a non-litigation dispute resolution mechanism rooted in the principles of justice and deliberation as enshrined in Islamic law. This study aims to examine the legal foundations of sharia arbitration and its position as an alternative dispute resolution mechanism under Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution. The research adopts a normative legal approach by analyzing primary legal sources, including the Qur’an, the Hadith of the Prophet Muhammad (peace be upon him), as well as national statutory regulations, particularly Law No. 30 of 1999, the Compilation of Sharia Economic Law, and Supreme Court Regulation No. 14 of 2016. The findings indicate that the concepts of tahkim (arbitration) and sulh (amicable settlement) in Islamic law constitute the philosophical foundation of sharia arbitration in Indonesia, emphasizing the values of justice (‘adl), mutual consent of the parties, and deliberative consensus. Within the national legal framework, sharia arbitration attains juridical legitimacy through statutory recognition of arbitration as a civil dispute resolution mechanism outside the formal court system. Its implementation is carried out by institutions such as the National Sharia Arbitration Board (BASYARNAS) and BANI Sharia. Despite facing institutional and human resource constraints, sharia arbitration demonstrates strong prospects as an efficient and equitable dispute resolution mechanism